Sarcocystis spp. prevalence in bovine minced meat: a histological and molecular study - Serena Meistro (Italian Journal of Food Safety, 2015)
Sarcosporidiosis is caused by ingestion of contaminated raw or undercooked bovine meat and, although considered a minor zoonosis, it can represent a threath for immunocompromised people. Aim of this study was to determine the prevalence of Sarcocystis spp. in bovine minced meat intended for raw consumption collected from butcher shops and retail stores in Turin’s province (Piedmont region, Northwest Italy). Twenty-five samples were examined in parallel by histology and polymerase chain reaction (PCR). The prevalence of infestation of Sarcocystis spp. resulted to be 64% [confidence interval (CI) 95% 42- 82] and 88% (CI 95% 69-97) respectively by histology and PCR. In detail, the prevalence resulted 80% for S. cruzi (CI 95% 59-93), 68% for S. hominis (CI 95% 46-85) and 4% for S. hirsuta (CI 95% 0.10-20). The high prevalence of S. hominis highlights that sarcosporidiosis may constitute a public health problem in Italy, particularly in regions like Piedmont, that has traditional dishes prepared from raw or undercooked bovine meat.